Effect of Coffee Husk Compost and NPSB Fertilizers on Selected Soil Chemical Properties of Potato Field in Chora District, South West Ethiopia. (8th February 2022) - Jibril, Temam; Bekele, Getachew
Abstract : Field experiment was conducted in Chora District of south western Ethiopia, to evaluate the effect of different rates of coffee husk compost (CHC) and 18.9N + 37.7P + 6.94S + 0.15B (NPSB) in the form of NH4, P2 O5, SO4 −, and B2 O5, repectively, blended fertilizer on selected soil chemical properties of potato field during 2021. The treatment consisted of four rates of CHC (0, 2.5, 5, and 7.5 t ha −1 ) and four rates of blended NPSB fertilizer (0, 112.5, 150, and 187.5 kg ha −1 ). The experiment was laid out in randomized complete block design with three replications. Postharvest soil data were collected and subjected to ANOVA using SAS version 9.4. All the soil parameters analyzed were significantly (P < 0.05 ) affected by the main factors of CHC and NPSB blended fertilizer except exchangeable K + and Na + which were affected by main factors but not by factors interaction. The maximum pH (5.3), OC (6.0%), and CEC (14.10 meq 100g −1 ) were obtained from application of sole 7.5.t CHC ha −1 which is at par with combined 7.5.t CHC and 112.5 kg NPSB ha −1, while the maximum TN (26%), Av. P (3.57%), and Av. S (4.36%) were obtained from combined application of 7.5.t CHC and 112.5 kg NPSB ha −1 . The sole application of either of 150 kg or 187.5 kg NPSB ha −1 was resulted in high exchangeable acidity. Therefore, combined application of CHC and NPSB fertilizers raised the pH, improves the OC%, total N, available P and S, reduced the exchangeable acidity, and raises the CEC and exchangeable bases of potato field soil as compared to the control and sole NPSB fertilizer.